2021
DOI: 10.3389/fnut.2021.749328
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Induces Visceral Adipose Tissue Inflammation and Insulin Resistance Even Without Development of Obesity in Adult Female but Not in Male Rats

Abstract: Introduction: Obesity and related metabolic disturbances are frequently related to modern lifestyle and are characterized by excessive fructose intake. Visceral adipose tissue (VAT) inflammation has a central role in the development of insulin resistance, type 2 diabetes (T2D), and metabolic syndrome. Since sex-related differences in susceptibility and progression of metabolic disorders are not yet fully understood, our aim was to examine inflammation and insulin signaling in VAT of fructose-fed female and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 115 publications
0
22
0
Order By: Relevance
“…The same authors suggest a disrupted connection between the peripheral and central appetite regulatory mechanisms. Moreover, fructose-enriched diet has been shown to induce brain oxidative stress, including hypothalamic inflammation (Nabil et al 2020;Kovačević et al 2021), which could further contribute to the impaired signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors suggest a disrupted connection between the peripheral and central appetite regulatory mechanisms. Moreover, fructose-enriched diet has been shown to induce brain oxidative stress, including hypothalamic inflammation (Nabil et al 2020;Kovačević et al 2021), which could further contribute to the impaired signaling.…”
Section: Discussionmentioning
confidence: 99%
“…This puts the role of many additional factors (such as body composition, age, sex and insulin resistance), which may be of a significance for the peripheral hormonal responses in the energy homeostasis, appetite regulation and development of obesity (Yunker et al 2021). In a study of Kovačević et al (2021), fructose diet caused a greater extent of adipose tissue inflammation and insulin signaling impairment in female than in male rats. Interestingly, fructose overconsumption was not accompanied by obesity, which puts adipose tissue dysfunction at an earlier stage in the development of metabolic disorders and weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have demonstrated differences between high fat, high fructose or glucose, and a combination diet on numerous fatty liver related phenotypes including body weight, lipid and glucose metabolism, insulin resistance, and liver triglycerides 37,38 . Fructose, in particular, has been demonstrated as a major contributor to insulin resistance, increased body weight, oxidative stress, and in ammation [39][40][41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…A fructose-enriched diet induces the development of IR in the white adipose tissue of the adult female Wistar rats, although it did not lead to obesity and systemic IR. Thus, the protein levels of SOD1 and GR were increased in white adipose tissue of fructose-fed female rats, compared to the control group, which probably serve to prevent intracellular RONS accumulation and oxidative damage of macromolecules [78]. However, as obesity progresses, the amount and activity of the AOS components become depleted, increasing susceptibility to oxidative tissue damage [79].…”
Section: Evidence From Animal Studiesmentioning
confidence: 98%
“…Moreover, the administration of the insulin-sensitizing drug pioglitazone to HFCD-induced IR rats reduced MDA level and improved GSH level, compared to the non-treated IR-induced group of rats [83]. Perirenal, epididymal, and brown adipose tissues of male Wistar rats SOD, CAT, GPx activities Decreased [82] Liver of male C57BL/6 mice Mn-SOD protein level Decreased [29] Heart of male C57BL/6J mice CAT protein level/CAT activity Increased [76] Visceral adipose tissue of female Wistar rats Mn-SOD, GPx protein levels/Cu/Zn-SOD, GR protein levels Decreased/unchanged [81] Primary hepatocytes of male C57BL/6J mice GSH content, GPx, and GR activities Decreased [31] Soleus muscle of Wistar male rats Total GSH level/Mn-SOD, CAT, GPx expression Decreased/unchanged [77] Plasma samples and heart of male fa/fa ZR SOD/GPx activities Decreased/unchanged [30] Serum of male Albino rats MDA level/GSH level Increased/decreased [83] White adipose tissue of female Wistar rats SOD1 and GR protein levels Increased [78] Ref: reference…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%